(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
Amidst growing political division and strife, the Russian and Ukrainian peoples are united by a common faith—Orthodoxy. While much literature and punditry offer commentary on the widening chasm between the region’s two predominant iterations of Orthodoxy—Russian and Ukrainian—this author provides a synthesis of religious and sociopolitical history to illuminate the sects’ common beginnings and constitutions. As a result, the author finds that it is not Orthodoxy itself that has fractured the two peoples. Rather, it is strategic usury and politicization that have corrupted Orthodoxy in the post-Soviet space. In response, the author suggests a return to the simplicity of orthodox Orthodoxy, the augmentation of believers’ perceptions of one another, and perhaps a bit of ‘holy foolishness.’ For additional context, listen to the author’s reflection on the piece below.